Glibenclamide reduces secondary brain damage after experimental traumatic brain injury - Zweckberger, Klaus; Hackenberg, Katharina; Jung, Carla Sabine; Hertle, Daniel; Kiening, Karl; Unterberg, Andreas; Sakowitz, Oliver (Neuroscience, 2014)
Following traumatic brain injury (TBI) SUR1-regulated NCCa-ATP (SUR1/TRPM4) channels are transcriptionally up-regulated in ischemic astrocytes, neurons, and capillaries. ATP depletion results in depolarization and opening of the channel leading to cytotoxic edema. Glibenclamide is an inhibitor of SUR-1 and, thus, might prevent cytotoxic edema and secondary brain damage following TBI. Anesthetized adult Sprague-Dawley rats underwent parietal craniotomy and were subjected to controlled cortical impact injury (CCI). Glibenclamide was administered as a bolus injection 15min after CCI injury and continuously via osmotic pumps throughout 7days. In an acute trial (180min) mean arterial blood pressure, heart rate, intracranial pressure, encephalographic activity, and cerebral metabolism were monitored. Brain water content was assessed gravimetrically 24h after CCI injury and contusion volumes were measured by MRI scanning technique at 8h, 24h, 72h, and 7d post injury. Throughout the entire time of observation neurological function was quantified using the “beam-walking” test. Glibenclamide-treated animals showed a significant reduction in the development of brain tissue water content(80.47%±0.37% (glibenclamide) vs. 80.83%±0.44% (control); p<0.05; n=14). Contusion sizes increased continuously within 72h following CCI injury, but glibenclamide-treated animals had significantly smaller volumes at any time-points, like 172.53±38.74mm3 (glibenclamide) vs. 299.20±64.02mm3 (control) (p<0.01; n=10; 24h) or 211.10±41.03mm3 (glibenclamide) vs. 309.76±19.45mm3 (control) (p<0.05; n=10; 72h), respectively. An effect on acute parameters, however, could not be detected, most likely because of the up-regulation of the channel within 3-6h after injury. Furthermore, there was no significant effect on motor function assessed by the beam-walking test throughout 7days. In accordance to these results and the available literature, glibenclamide seems to have promising potency in the treatment of TBI.